Impact of Volcanic Eruptions on the Occurrence of PAHs Compounds in the Aquatic Ecosystem of the Southern Part of West Spitsbergen (Hornsund Fjord, Svalbard) - Katarzyna Kozak; Marek Ruman; Klaudia Kosek; Grzegorz Karasiński; Łukasz Stachnik; Żaneta Polkowska (Water, 2017)
The paper presents changes in concentration levels of dioxin-like compounds that can be observed over the course of four study seasons in water samples collected from the Arctic watershed of Svalbard. The conducted analysis involved anthropogenic and natural factors that may affect the concentration of PAHs in the study samples of water. An attempt is made to indicate the emission source of the compounds being deposited and to identify the extent to which the substances under analysis actually affect the Arctic ecosystems. Moreover, the work employs the following: diagnostic ratios PAHs, air masses backward trajectory analysis, Lidar observations and land relief analysis in order to provide a multi-level interpretation of the obtained data. Natural environment constitutes a complex system of subtle correlations that need to be perceived as a dynamic medium, in which multi-faceted processes take place.